2021
DOI: 10.3390/foods10071578
|View full text |Cite
|
Sign up to set email alerts
|

Application of Low Temperature during the Malaxation Phase of Virgin Olive Oil Mechanical Extraction Processes of Three Different Italian Cultivars

Abstract: The malaxation step, one of the most important phases of the virgin olive oil (VOO) mechanical extraction process involved in the development of the main quality characteristics of the final product, was carried out at a low temperature (18 °C). The rapid control of malaxer temperature was handled with the same chiller as that of the heat exchanger used in a semi-industrial extraction plant. Low temperature was used during the full olive paste kneading process and also for half of this process, which showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In addition, the introduction of heat exchangers in post-pressing, heating, or rapidly cooling the olive paste and changing the time of treatment according to the needs, can also promote the formation of all those compounds with sensory and health properties, as well as increase the yield [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the introduction of heat exchangers in post-pressing, heating, or rapidly cooling the olive paste and changing the time of treatment according to the needs, can also promote the formation of all those compounds with sensory and health properties, as well as increase the yield [9].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of controlling the temperature during the crushing phase allows us to determine the optimal conditions for some of the enzymes of the LOX pathway that showed higher activity levels at lower temperatures. The best performance of LOX enzymes was obtained with temperatures ≤ 20 °C, mainly due to the optimal activity of hydroperoxide lyase (HPL) for the conversion of 13-hydroperoxides into C 5 and C 6 aldehydes (Padilla et al, 2012;Salas & Sanchez, 1999;Veneziani et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The use of low temperatures can represent an alternative approach to modulate volatile compounds and preserve a higher concentration of hydrophilic phenols (Plasquy et al, 2021b;Veneziani et al, 2021). Alternative techniques to the regulation of the temperature of olives, such as the use of cold rooms to stabilize the temperature of fruits during the storage period (Guerrini et al, 2021;Morales-Sillero et al, 2017;Plasquy et al, 2021a;Taluri et al, 2019;Yousfi et al, 2012), the application of dry ice to cool the olives during the crushing phase (Veneziani et al, 2017;Zinnai et al, 2016), or the reduction of fruit temperature before processing by means of cold water (Dourou et al, 2020), were also tested to assess the impacts on EVOO quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study [ 11 ], performed at a laboratory scale to analyze the effects of different temperatures (20, 25, and 30 °C) and times (30 and 45 min) of malaxation on EVOO phenol content, demonstrated that the highest quality and highest content of phenolic compounds were obtained by 30 min of malaxation at 20 °C; an increasing trend of oxidation with temperature and time was also found. In [ 12 ], malaxation was carried out at a low temperature (18 °C) determining an overall reduction in the phenolic fraction of EVOOs while the impact on the volatile fraction, which influences the EVOO flavor, was found to be strongly cultivar-dependent. Malaxation, therefore, can enormously influence the characteristics of the final product on the basis of the process parameter management, extensively studied in the literature, i.e., time [ 13 ], temperature [ 14 ], and composition of the atmosphere in the headspace of the malaxer [ 15 ] with particular reference to oxygen.…”
Section: Introductionmentioning
confidence: 99%